About the main directions of modern Russian politics in the field of information counteraction to destructive political technologies - Yu. V. Usova; B. V. Tuaeva (Современная наука и инновации, 2023)
The article provides a comprehensive analysis of the conceptual foundations of the policy of the Russian Federation in the field of information counteraction to destructive political technologies, which involves identifying patterns and trends in ensuring the state security of the country, modeling and forecasting political processes in this area. Among the main directions for improving the practice of implementing the policy of the Russian Federation in the field of information counteraction, the information-ideological and information-psychological directions have been identified.